Antiarrhythmic effects and mechanisms of sodium-glucose cotransporter 2 inhibitors: A mini review - Wu, Jinchun; Liu, Yanmin; Wei, Xiaojuan; Zhang, Xiaofei; Ye, Yi; Li, Wei; Su, Xiaoling (Frontiers in Cardiovascular Medicine, 2022)
Sodium-glucose cotransporter 2 inhibitors (SGLT2i) are a new type of oral hypoglycaemic agent with good cardiovascular and renoprotective effects. Several lines of clinical evidence suggest that SGLT2 inhibitors can significantly reduce the risks of atherosclerosis, hospitalization due to heart failure, and cardiovascular death and delay the progression of chronic kidney disease. In addition, recent basic and clinical studies have also reported that SGLT2i also have good anti-arrhythmic effects; however, the exact mechanism is poorly understood. In this review, we summarize the recent clinical evidence of the antiarrhythmic effects, underlying mechanisms, safety, and prospects for clinical applications.